2017 anayasa referandumunun AİHS 1 nolu protokol madde 3 kapsamında değerlendirmesi - Arslan, Amine (My University, 2025)
2017 anayasa referandumunun AİHS 1 nolu protokol madde 3 kapsamında değerlendirmesi 2017 Anayasa Referandumu, parlamenter hükümet sistemi pratiğini terk ederek Türkiye’nin siyasi tarihinde önemli bir rota değişikliğine yol açmıştır. Yeni sistem özgün yönleri olan, erkeler arasında güç asimetrisinin tesis edildiği ve yürütmenin ön plana çıktığı bir dizayna sahiptir. Bu denli önemli nitelikteki referandumun meşruiyeti, seçimlerin serbestliği ve denetim mekanizmalarının yeterliliği bakımından ciddi tartışmalara yol açmıştır. Bu çalışmada, söz konusu referandum AİHS’in demokrasi anlayışı ve serbest seçim hakkının düzenlendiği P1M3 bağlamında değerlendirilmektedir. Öncelikle AİHS’i ortaya çıkaran tarihi ve siyasi arka plan çerçevesinde Sözleşmenin demokrasi temeli incelenmiş, ardından AİHM içtihatlarında demokrasi kavramı ele alınmıştır. İkinci bölümde, serbest seçim hakkının kapsamı, sınırları ve AİHM’in yorum pratiği analiz edilmiştir. Son bölümde ise 2017 Anayasa Referandumunun yarattığı uyuşmazlıklar AİHM’in konuya yaklaşımıyla birlikte tartışılmıştır. Elde edilen bulgular, AİHS sisteminin otoriterleşme karşısında “erken uyarı mekanizması” olarak tasarlandığını ancak günümüzün demokratik aşınmalarına karşı yetersiz kaldığını göstermektedir. AİHM’in referandumları P1M3’ün kapsamı dışında bırakması, Sözleşme’nin demokrasiyi koruma amacında yapısal bir boşluk yaratmaktadır. Protokol 1 madde 3’ün lafzı dikkate alındığında, mevcut sorunun yorum yoluyla giderilmesi mümkün görünmemektedir. Bu nedenle Avrupa Konseyi’nin, serbest seçim hakkını çağın gereksinimlerine uygun biçimde yeniden tanımlanması gerektiği kanaatine varılmıştır.

An assessment of the 2017 constitutional referendum under article 3 of protocol no. 1 to the echr The 2017 Constitutional Referendum marked a significant turning point in Turkey’s political history by abandoning the long-standing practice of the parliamentary system. The newly established system, characterized by its unique design, institutionalized an asymmetry on the power division and elevated the executive power to a dominant position. The legitimacy of such a highly significant referendum has given rise to serious debates concerning the freedom of elections and the adequacy of oversight mechanisms. In this study, the referendum in question is evaluated within the context of the ECHR’s understanding of democracy and A3P1, which guarantees the right to free elections. The first part explores the historical and political background that led to the drafting of the ECHR and examines the democratic foundations of the Convention, followed by an analysis of how ECtHR has conceptualized democracy through its jurisprudence. The second part analyzes the scope and limitations of the right to free elections and the Court’s interpretative approach, while the final section discusses the legal and political disputes arising from the 2017 Constitutional Referendum in light of the Court’s stance. Findings demonstrate that while the ECHR system was designed as an “alarm bell” against authoritarianism, it has proved inadequate in addressing contemporary forms of democratic erosion. The ECtHR’s exclusion of referendums from the scope of A3P1 creates a structural gap in the Convention’s democratic safeguard. Considering the wording of Article A3P1, it appears that the existing issue cannot be resolved through interpretation. Therefore, it has been concluded that the Council of Europe should redefine the right to free elections in a manner that reflects the requirements of the modern era.
An assessment of the 2017 constitutional referendum under article 3 of protocol no. 1 to the ECHR
Keywords: 1 Nolu Protokol Madde 3; 2017 Anayasa Referandumu; 2017 Constitutional Referendum; Anayasa hukuku --Türkiye; Article 3 of Protocol No. 1; Avrupa İnsan Hakları Mahkemesi; Avrupa İnsan Hakları Mahkemesi (AİHM); Avrupa İnsan Hakları Sözleşmesi; Avrupa İnsan Hakları Sözleşmesi (AİHS); Constitutional law; Decision on Unstamped Ballots; Democracy; Demokrasi; Electoral Law; European Convention of Human Rights; European Court of Human Rights; Human rights; İnsan hakları; Mühürsüz Oy Kararı; Right to Free Elections; Seçim Hukuku European Convention on Human Rights; Serbest Seçim Hakkı; Supreme Election Council; Turkey; Yüksek Seçim Kurulu